Analysis of human body surface shape using parametric design method. Issue 3 (1st June 2015) - Kim, Sungmin
Abstract : Purpose: – The purpose of this paper is to analyze automation of body surface shape. Design/methodology/approach: – Numerous body landmarks are detected automatically. Body surface can be subdivided into multiple patches in a consistent manner using parametric design method. Findings: – Complex surface shape of various human bodies can be analyzed easily and consistently. Research limitations/implications: – The proposed method may not be applicable for a body with the shape which significantly differs from that of an average body. Practical implications: – This method can greatly reduce the time required to analyze the surface shape of a three dimensional body scan data. Originality/value: – The analysis of body surface shape is one of the most important processes especially in designing close fitting garments. The parametric design of body surface patches will facilitate the analysis of numerous body scan data.